Deskripsi Interaksi Sosial Anak Usia Dini Di Kelompok B TK Helim - Dewi Rahmatia Habie; Ardini, Pupung Puspa; Jamin, Nunung Suryana (Student Journal of Early Childhood Education, 2024)
This study aims to analyze social interactions in early childhood with friends in Group B Helim Kindergarten. This study uses a descriptive qualitative method involving 3 informants, consisting of 1 school principal, I class B teacher, and I class B student. Findings showed that children were still able to interact with their friends, even though there were many obstacles that the teacher experienced in the learning process, such as children not wanting to learn because they were used to holding cellphones and often fussy in class. In conclusion, some children do not want to interact with teachers and their friends, but teachers still provide stimulating support for children to with their friends and not be shy anymore. Therefore, children can interact more optimally and begin to get used to interacting.